Pengaruh Harga Jual terhadap Volume Penjualan Rokok (Studi Kasus pada Perusahaan Subsektor Rokok yang terdaftar di Bursa Efek Indonesia) - Rospita Sari, Cici; Indrawati, Lili; Sembiring, Etti Ernita; Ishak, Jouzar Farouq (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
After the economy slowed down due to the pandemic, demand in the cigarette sector began to recover in 2021. The growth rate of cigarette sales volume is different for each category. These conditions indicate that the price gap due to CHT tariffs has led to significant growth in the performance of products at lower prices (IDX, 2022). This study uses a quantitative approach using the selling price (X) and sales volume (Y). The subjects are 3 cigarette sub-sector companies that are listed on the Indonesia Stock Exchange and have published their 2017-2021 annual reports. Data were analyzed using panel data regression with the help of SPSS 26.0 software. The results showed that the selling price variable had a significant positive effect on sales volume. This can be seen from the results of the t test where the significance value of the t test is 0.003 <0.05. In addition, the coefficient of determination shows that the selling price variable has an effect of 49.7% on sales volume. While the remaining 50.3% is influenced by other factors not included in this study.